Pregnancy and multiple sclerosis - Airas, Laura (Obstet Med, 2012)
The relapse rate of multiple sclerosis (MS) is typically reduced during late pregnancy but increases in the postpartum period. The reasons for the increased postpartum activity are not entirely clear, but factors such as the abrupt decrease in oestrogen levels immediately after the delivery and the loss of the immunosuppressive state of pregnancy are likely of importance. There is a general view that MS does not affect the course or outcome of pregnancy.